Broadcasting Communications in Encouraging Public Participation in Elections - Syafii, Akhmad; Elya Rohimi, Upit; Shobichah, Shobichah; Atikah, Nila; Rani, Prieska (Journal of World Science, 2023)
Introduction: Public participation in regional elections is still quite low, even though regional elections are a form of implementing democracy in Indonesia. Broadcasting communications can play an important role in encouraging public participation in Pilkada. Therefore, this study aims to identify and analyze the effectiveness of broadcasting communication strategies in encouraging public participation in regional elections. Method: This study uses a qualitative approach with data collection techniques through in-depth interviews with informants related to the Pilkada and broadcast media. Result: The results of the study show that broadcast media can be used as an effective means of communication to increase public participation in regional elections by conveying appropriate and balanced information and facilitating public discussion of election-related issues. Several effective strategies for encouraging public participation in Pilkada through broadcast media include using attractive campaign jingles, wider coverage of candidates and their work programs, and public debates between candidates, which are broadcast live. Conclusion: Broadcast media is an effective means of communication to increase public participation in local elections by conveying appropriate, balanced information and facilitating public discussion on issues related to local elections.